Similarities and differences in parenting patterns for children with disabilities and normal children in motivating children's independence in Kampung Ketapang Hilir Pekan Pahang, Malaysia: (case study in the family of Mr. Arif) - Razak, Nurul Fathiah binti Abdul; Samosir, Hasrat Efendi; Penulis, Winda Kustiawan (International Journal on Social Science, Economics and Art, 2024)
The researcher is interested in examining the similarities and differences in parenting patterns for children with tunagrahita and normal children in motivating children's independence. The purpose of this study is to determine the similarities and differences in parenting patterns of parents of children with disabilities and normal children in motivating children's independence in Kampung Ketapang Hilir, Pekan Pahang, Malaysia. This study uses a research method with a case study approach. Case study research is a form of qualitative research based on understanding and action based on human opinion. The data collection techniques used are observation, interviews and documentation. Based on the analysis that has been done, this article discusses the following findings: 1) The form of parenting given by parents to children with disabilities and normal children in motivating children's independence. 2) Parenting methods given by parents to children with disabilities and normal children in motivating children's independence. 3) Scattering of parents in motivating the independence of deaf and normal children. From the results of this study, the parenting pattern used is democratic parenting, where parents make normal children and tunagrahita children independent and look after each other.